2005
DOI: 10.1210/jc.2004-0240
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic Screening and Follow-Up in Patients with Acromegaly: A Multicenter Study in Italy

Abstract: Acromegaly is an infrequent disease attributable to endogenous excess of GH and IGF-I. Human studies have associated the GH-IGF-I axis with the development of colorectal cancer; however, the question of whether colorectal cancer is a problem in acromegaly is currently unresolved. We performed a cross-sectional study to assess the risk of colonic neoplasia in patients with acromegaly. Colonoscopic screening was performed in 235 patients with acromegaly at five tertiary care hospitals in Italy between January 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 56 publications
6
82
1
7
Order By: Relevance
“…In our original series, we observed 5% to have a carcinoma and 25% to have one or more adenomas (11). Similar findings have been reported by other groups (12). In the non-acromegalic population, the vast majority of colorectal cancers derive from adenomatous polyps through the progressive accumulation of mutations in oncogenes and tumour suppressor genes, a process that takes w10-20 years (13,14).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our original series, we observed 5% to have a carcinoma and 25% to have one or more adenomas (11). Similar findings have been reported by other groups (12). In the non-acromegalic population, the vast majority of colorectal cancers derive from adenomatous polyps through the progressive accumulation of mutations in oncogenes and tumour suppressor genes, a process that takes w10-20 years (13,14).…”
Section: Introductionsupporting
confidence: 89%
“…Several previous studies have suggested that these patients are also at an increased risk of neoplasia, especially colorectal cancer and pre-malignant adenomatous polyps, although the degree of risk remains under debate (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In our original series, we observed 5% to have a carcinoma and 25% to have one or more adenomas (11).…”
Section: Introductionmentioning
confidence: 51%
“…Some studies have shown a higher frequency of differentiated thyroid carcinomas in acromegalic patients (16,21,22) due to the increased level of GH and IGF-I. Calculated risk of thyroid cancer in these patients appears to be sixty-fold higher than in the overall population (23,24).…”
Section: Discussionmentioning
confidence: 96%
“…Despite the variation of polyps and cancer prevalence at this site (9-38%) in different series (12)(13)(14)(15)(16), the correlation between acromegaly and tumors is frequently observed, and many studies have shown that an increase in IGF-I is correlated with an increase in the prevalence of polyps (12,13), adenomas (17) and proliferation of colon epithelium cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…Some only consider it at 50-55 years (Renehan et al 2001), but even younger patients harbor colonic tumors, so initial colonoscopy at ACM diagnosis has been suggested (Terzolo et al 2005). Repeated colonoscopy every 10 years in controlled ACM with a normal initial result and every 5 years in those with benign tumors or uncontrolled disease appears reasonable (Dworakowska et al 2010).…”
Section: Complicationsmentioning
confidence: 99%